STUDENTS’ MOTIVATIONS IN ENGLISH LANGUAGE LEARNING OF EFL CLASSROOM: A CASE STUDY OF ENGLISH DEPARTMENT STUDENTS OF ACADEMIC YEAR 2018/2019 IKIP SILIWANGI BANDUNG - Husnussalam, Hendra; Sudiyono, Sudiyono; Rahayu, Silpia (IKIP Siliwangi, 2020)
Some psychologists and educationalists have explained various models related to students’ motivation in learning English language. One of them is proposed by (Gardner, 1988) who explained about the socio-educational model. This study reports data from the interview conducted to the English Department students of IKIP Siliwangi of Academic Year 2018/2019 about their motivation in English language learning. In this research, there are three students of English Department as the participants. In addition to the researcher, the instrument of this study is Interview which is applied to the three students based on their language ability levels; namely, high, moderate and low. This study belongs to Qualitative research because there is no statistical data presented. Instead, the data were collected by using structured interview and then, they were transcribed, categorized and interpreted. The findings revealed that there are three factors for the students that makes the students of English Department becomes more motivated in English language learning; namely, the teacher himself, the teaching strategies and games. Keywords: Students’ Perception, English Language, Traditional Classroom